Soil chemical Fertility for maize in Tibawa, Gorontalo, Indonesia - Ferawati Bano; Zulzain Ilahude; Nurmi; Rida Iswati; Laode Muhamad Irsan (International journal of technology and education research, 2026)
This study evaluated the chemical status of soils under maize (Zea mays L.) cultivation in Tibawa Subdistrict, Gorontalo Regency, Indonesia, to identify fertility constraints and inform site-specific management. A field survey was conducted in May 2025 at three villages (Isimu Utara, Datahu, and Iloponu). At each site, ten subsamples from the 0–20 cm plough layer were composited and analysed for soil pH (H2O and KCl), organic carbon, total nitrogen (Kjeldahl), available phosphorus (Bray I), exchangeable potassium (NH4OAc), and cation exchange capacity (CEC). Results indicated slightly acidic to neutral soils (pH 6.3 - 6.9) with moderate CEC (16.72 - 22.32 cmol(+)/kg). Organic carbon ranged from low to moderate (1.42 - 2.51%). Available P was consistently moderate (12.04–14.72 ppm), whereas exchangeable K was low across all sites (0.19 - 0.24 cmol(+)/kg). Total N varied from low in Isimu Utara (0.13%) to moderate in Datahu and Iloponu (0.24 - 0.26%). The primary limitations for maize production were low K availability and, locally, low N and organic matter. Management should prioritize organic amendments, balanced NPK fertilization based on soil testing, and periodic liming where acidification trends emerge. These findings provide a baseline for future monitoring of soil quality and developing recommendations to sustain maize yields while reducing nutrient losses under intensive management in Tibawa.